2017
DOI: 10.1186/s12957-016-1078-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors for early recurrence of resectable pancreatic cancer

Abstract: BackgroundThe first-line treatment for resectable pancreatic cancer (RPC) is surgical resection. However, our patients have often experienced early recurrence after curative resection for RPC, with desperately poor prognosis. Some reports indicated that minimally distant metastasis not detected at operation might cause early recurrence. The present study aimed to identify preoperative clinicopathological features of early recurrence after curative resection of RPC.MethodsNinety RPC patients who underwent curat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 35 publications
3
95
0
Order By: Relevance
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane Collaboration tool for assessing risk of bias showed that one study had no domain with a high risk of bias and three studies had one of seven domains with a high risk of bias ( Table S3 , supporting information). The overall risk of bias in non‐randomized studies, according to ROBINS‐I, was moderate in 48 studies and serious in 37 studies ( Table S4 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…A longer median survival and greater 5-year survival rate have been observed among patients with either normal or undetectable preoperative levels of CA19-9 compared to patients having elevated levels [26]. Until now, some studies have reported that the preoperative serum CA19-9 level is a significant predictor of early recurrence after resection for PDAC [4, 13, 27]. The cutoff value for serum CA19-9 level in a few reports was as high as 590–2,000 U/mL, but some reports used a level as low as 100 U/mL [4, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, only 9 out of 108 (8.3%) patients with successfully resected disease had peripherally detected KRAS mutations. Only 4.6 percent of patients with a negative preoperative ctDNA-based liquid biopsy insuffered distant recurrences within 6 months of surgery, compared with 35% in a separate study with radiographically defined resectable disease, but no liquid biopsy testing [ 83 , 84 ]. Thus, radiographic staging and then further stratification with ctDNA may optimize the selection of patients who would benefit from surgical resection.…”
Section: Current Clinical Utility Of Cfdnamentioning
confidence: 99%
“…Recurrence after curative-intent therapy is high in PDAC. One study of patients with early stage, resectable disease demonstrated 35% recurrence at 1-year follow up, while 1-year recurrence rates over 80% have been observed in patients with borderline resectable disease [ 84 , 90 ]. Early detection of recurrences is key to initiating appropriate systemic therapy.…”
Section: Current Clinical Utility Of Cfdnamentioning
confidence: 99%